Neurological disorders in famous artists - Part 2: more on the relationship between brain disease and creativity - Bogousslavsky, Julien (Frontiers of neurology and neuroscience, 2007)
‘Neurological Disorders in Famous Artists - Part 2’ presents more writers, philosophers, musicians, painters and film directors who developed some form of neurological dysfunction and whose style and output changed following a stroke or other cerebral disorder. Mozart, Baudelaire, de Kooning, Proust, Füssli, Heine, Fellini, Visconti and others are all striking examples of how extraordinary creativity can be challenged and modified or destroyed and restored, all within the drama of a disease. When brain disease challenges the capabilities of artists, the changes that subsequently occur in their work provide a unique opportunity to explore the mysteries of creativity. This may also lead to a better understanding on how certain artists developed, particularly when the course of a disease corresponds with what is generally recognized as a new chapter in their work.This book offers a fascinating read for neurologists, psychiatrists, general physicians and anybody interested in art, literature, music and film